2015
DOI: 10.1158/0008-5472.can-14-1801
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Upregulation of EGFR Limits Attenuation of Tumor Growth by Neutralizing IL6 Antibodies, with Implications for Combined Therapy in Ovarian Cancer

Abstract: Excess production of the proinflammatory IL6 has both local and systemic tumor-promoting activity in many cancers, including ovarian cancer. However, treatment of advanced ovarian cancer patients with a neutralizing IL6 antibody yielded little efficacy in a previous phase II clinical trial. Here, we report results that may explain this outcome, based on the finding that neutralizing antibodies to IL6 and STAT3 inhibition are sufficient to upregulate the EGFR pathway in high-grade serous and other ovarian cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…Most therapeutic antibodies have failed in phase II/III clinical trials due to the lack of biomarkers to identify the subset of patients most likely to benefit from a specific targeted therapy. A few studies have reported that cells compensate for the presence of a neutralizing antibody by activating another oncogenic signaling pathway . According to these reports, it is worth investigating the targeting of multiple pathways with companion biomarkers, such as targeting both VEGF and IL‐6 or both EGFR and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…Most therapeutic antibodies have failed in phase II/III clinical trials due to the lack of biomarkers to identify the subset of patients most likely to benefit from a specific targeted therapy. A few studies have reported that cells compensate for the presence of a neutralizing antibody by activating another oncogenic signaling pathway . According to these reports, it is worth investigating the targeting of multiple pathways with companion biomarkers, such as targeting both VEGF and IL‐6 or both EGFR and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IL6 secretion and consequent autocrine survival signaling were also found to be a cause of drug resistance to the EGFR inhibitor, erlotinib, in NSCLC (12). Conversely, IL6 antibody treatment can upregulate EGFR expression and limit ovarian tumor growth inhibition (39). This suggests that a combined approach blocking both the EGFR and IL6 pathways may improve response and counteract resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The AOCS1 cell line was kindly given by Professor David Bowtell (Peter MacCallum Cancer Centre, Melbourne, Australia) and was established from the ascites of a patient diagnosed with HGSOC, Silverberg Grade 3, after second relapse.The G33 cell line was established in our laboratory from an omental HGSOC tumor collected during interval debulking surgery in 2011 (16). The cell lines have been authenticated.…”
Section: Methodsmentioning
confidence: 99%